"Occult" mastocytosis with activating c-kit point mutation evolving into systemic mastocytosis associated with plasma cell myeloma and secondary amyloidosis. Issue 8 (27th July 2006) - Sotlar, K; Saeger, W; Stellmacher, F; Stahmer, J; Jäckle, S; Valent, P; Horny, H-P
Abstract : A case of a 70-year-old man presenting with exsudative enteropathy due to light-chain-associated amyloidosis is reported. The diagnosis of systemic mastocytosis associated with IgG/λ plasma cell myeloma and secondary generalised amyloidosis was carried out by morphological evaluation of bone marrow biopsy. The c-kit point mutation D816Y was detected by molecular analysis. Two years before, a cystadenolymphoma of the left parotid gland had been removed. A moderate increase of loosely scattered spindle-shaped mast cells, a subpopulation of them expressing CD25, an antigen that is not expressed by normal or reactive mast cells, was shown by retrospective analysis carried out on an intraparotideal lymph node. The c-kit mutation D816Y was shown by the molecular analysis of the lymph node. In summary, the notion that systemic mastocytosis may very rarely be associated with B cell neoplasms and that neoplastic mast cell infiltrates may be obscured because of only a minimal increase of atypical mast cells, which are outnumbered by other non-neoplastic cells in the same tissue, is supported by this case. This finding was preliminarily termed "occult" mastocytosis.